ANALISIS KEMANDIRIAN BELAJAR PADA SISWA KELAS X SMA KEMALA BHAYANGKARI SUNGAI RAYA - Thoken, Florensius; Asrori, Asrori; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning Independence is an awareness of the student as a student, he must be responsible for his need to acquire certain knowledge or skills on his own without any dependence from others. The independence of this learning can affect student learning outcomes, because with the independence in learning, the students have a responsibility to the learning process and do their best to succeed in learning in order to obtain the value of learning results are satisfactory and proud. A common problem in this research is how is student's independence in class X SMA Kemala Bhayangkari Sungai Raya?. The method used is descriptive method and the research form is survey study. The sample in this research is 51 students. This research uses quantitative research. Data collection techniques used are indirect communication techniques in the form of questionnaires. Data analysis techniques using the formula percentage. Based on the results of data analysis research student self-reliance achieved the score in the category of "Good". this shows that the independence of students in grade X SMA Kemala Bhayangkari can be said good. Keywords: Kemandirian, Belajar, Siswa SMA